1991
DOI: 10.1055/s-2008-1033318
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Wertigkeit von Mn-DPDP: Neues paramagnetisches hepatobiliäres Kontrastmittel für die Magnetresonanztomographie der Leber

Abstract: In an open prospective study the tolerance and diagnostic value of the new hepatobiliary contrast agent Mn-DPDP in MR imaging was evaluated in 20 patients suspected of having focal liver lesions. T1- and T2-weighted spin-echo sequences and T1-weighted gradient-echo sequences were obtained before and after intravenous application of Mn-DPDP. In all patients the signal to noise (S/N) values of normal liver tissue increased significantly after application of Mn-DPDP. All focal lesions could be better localized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prior to the development of Gd-EOB-DTPA, the Mn(II) complex of DPDP [86]—mangafodipir (Figure 2)—was clinically approved in the 1990s as a hepatobiliary CA. Mangafodipir-enhanced MRI improved the identification of HCC [18,87,88] and more generally the detection, classification, and diagnosis of focal liver lesions (Figure 3) [24,89,90,91,92], including primary and metastatic liver tumors [93,94]. Excellent articles have been published comparing liver-specific Gd-EOB-DTPA, Gd-BOBPTA, and Mn-DPDP with detailed descriptions of detection rates, contrast enhancement on various types of lesions, and influence on the respective acquisition techniques [90].…”
Section: Metal Complexes In Liver Specific Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the development of Gd-EOB-DTPA, the Mn(II) complex of DPDP [86]—mangafodipir (Figure 2)—was clinically approved in the 1990s as a hepatobiliary CA. Mangafodipir-enhanced MRI improved the identification of HCC [18,87,88] and more generally the detection, classification, and diagnosis of focal liver lesions (Figure 3) [24,89,90,91,92], including primary and metastatic liver tumors [93,94]. Excellent articles have been published comparing liver-specific Gd-EOB-DTPA, Gd-BOBPTA, and Mn-DPDP with detailed descriptions of detection rates, contrast enhancement on various types of lesions, and influence on the respective acquisition techniques [90].…”
Section: Metal Complexes In Liver Specific Mrimentioning
confidence: 99%
“…Free Mn(II) has been associated with extensive production of reactive oxygen species (ROS) [104,105], reactive nitrogen species (RNS) [106], and also with mitochondrial manganese superoxide dismutase (MnSOD) mimetic activities [107]. Also, possible adverse cardiovascular responses such as negative inotropy and vasodilation were suspected to occur based on the fact that Mn(II)—particularly if released at high extracellular concentrations—may act as a clinically-relevant Ca(II) antagonist [88,108,109]. However, early studies focused on toxicity and cardiovascular effects have concluded that Mn-DPDP is generally safe in normal clinical use [90,110,111].…”
Section: Metal Complexes In Liver Specific Mrimentioning
confidence: 99%